Аналіз поселень Ярославського повіту від другої половини ХVІІІ століття із застосуванням GIS - Козак, І.; Козак, Г. (Краєзнавство, 2016)
Дослідження проведено в актуальних межах Ярославського повіту (powiat Jarosławski) Підкарпатського воєводства (województwo Podkarpackie) у східній Польщі. Проаналізовано динаміку
поселень у Ярославському повіті від другої половини XVIII століття. Для цього застосовано
карти та опубліковані історичні дані, які проаналізовано у програмі ArcGIS 10.3. У праці показано можливості програми ArcGIS. Територію повіту досліджено під кутом зору змін поселень. До аналізу змін структури поселень використано серію карт (із бази «WIG» та із сервера
«WMS»). Показано зміни кількості сіл, чисельності господарств та динаміку чисельності українців у порівняні до чисельності поляків. Охарактеризавано національний та релігійний склад
від другої половини XVIII століття. На основі дослідження просторового розміщення поселень
із застосуванням просторової статистики (тест просторової автокореляції Морана, аналіз
еліпсів стандартних відхилень та аналіз середніх географічних центрів) показано характер
поселень в актуальних межах Ярославського повіту. The study was conducted within the actual area of Jaroslav district in Podkarpackie voivodeship
in Eastern Poland. The dynamics of settlements in the Jaroslav district from the 2nd half of the 18th
century was discussed. Maps and historical data were analyzed in the ArcGIS 10.3 program. In the
study there were presented possibilities of applying the ArcGIS for Desktop 10.3 program. We analyzed
the Jaroslav district in terms of the changes of settlements and used maps for the analysis of changes
in its structure. The first of these was the historical map, namely the tactical map of WIG in scale 1:
100 000 from 1936. Next we analyzed maps from 1965 and 2014, which were prepared applying the
WMS server. The changes in the number of villages, households and population dynamics of Ukrainians
were shown in comparison with the number of Poles. Ethnic and religious composition from the
2nd half of the 18th century were evaluated. Based on the study of spatial placement of settlements with
the use of Spatial Statistics (Spatial Autocorrelation Global Moran’s test, Standard Deviational Ellipse
and Central Feature) the character of settlements distribution in Jaroslav district was presented. There
was confirmed a similar configuration of Standard Deviation Ellipses and Mean Center for Greekcatholic
and Ukrainians in Jaroslav district. The scale and results of such changes are interesting for
future research, mainly in terms of the change of traditional village infrastructure and its culture. Исследование проведено в актуальных пределах Ярославского района в восточной
Польше. Проанализировано динамика селений в Ярославском районе со второй половины
18 века. Для этого использованы карты и опубликованные исторические данные, которые
проанализировано в программе ArcGIS 10.3. Показано изменения количества сел, численности хозяйств и динамику численности украинцев по сравнению с численностью поляков.
Охарактеризовано национальный и религиозный состав со второй половины 18 века. На основе исследования пространственного размещения поселений с применением статистических анализов (тест Морана пространственной автокореляции, эллипс стандартных отклонений и центральний объект) показано естественный и длительный характер украинских поселений в Польше.